Rancang Bangun System Informasi Pelayanan Dan Konsultasi Berbasis Web Menggunakan Model Waterfall (Studi Kasus : Klinik Pratama dr.JO) - Winarno, Agus; Zakaria, Hadi; Udin Zaelani, Achmad; Ardhiansyah, Maulana (CV. Shofanah Media Berkah, 2023)
Dr.Jo’s clinic for beauty and aesthetics who had a concern for excellent services. The services that customers choose one is beauty service, mostly in a month there’s 4500 patience who using the clinic’s services. For using the services of this clinic, patients have to register for the first place, in this case, there are usually people gonna make a line and waiting too long. This problem also happened because the patient didn’t know the schedule of the doctor in charge for that day. For the solutions, clinics need an Information System Service based on WEB using a PHP Program and MY SQL Database. With the information system Service, clinics could avoid the line case when doing registration on the spot because the data was recorded before using online registration. With Information System Service, we avoiding the line of registration and the patient can check the doctor’s schedule, and the patient could arrange the meeting properly and having a consul hour following their schedule.